Unambiguous Stacking Fault Analysis for Unraveling Shearing Mechanisms and Shear-Based Transformations in the L12-Ordered γ′ Phase - Karpstein, N.; Lenz, Malte; Bezold, Andreas; Zehl, R.; Wu, Mingjian; Ludwig, A.; Laplanche, G.; Neumeier, Steffen; Spiecker, Erdmann (Proceedings of the 15th International Symposium on Superalloys, 2024)
With its precipitation strengthening effect, the L12-ordered γ′ phase contributes substantially to the mechanical properties of superalloys; therefore, understanding the microscopic mechanisms by which it can be sheared is of key importance. A commonly used method to study these mechanisms involves high-resolution imaging in the transmission electron microscope in <110> projection which enables straightforward discrimination between intrinsic and extrinsic stacking faults as well as microtwins. However, the complex or superlattice nature of these stacking fault structures, which provides key information on their formation mechanism, is not necessarily revealed in this projection. In the present work, an experimental approach is presented to resolve this ambiguity and reliably determine the complex or superlattice nature of a stacking fault in the L12 structure by additionally imaging the fault in a nearby <211> projection, which is achieved by tilting the specimen by 30°. The method is demonstrated using two different examples in single-crystalline Co-base superalloys. In the first example, the approach enabled the direct experimental verification of two key aspects of the well-known Kolbe mechanism for superlattice extrinsic stacking fault formation, namely, the complex nature of the leading intrinsic stacking fault segment and the occurrence of diffusion-mediated re-ordering. In the second example, microscopic details of the shear-based transformation from the cubic L12-γ′ to the hexagonal D019-χ phase are revealed, accounting for additional complexities—again including a re-ordering process—arising from the superlattice ordering of both phase
CRIS-Team Scopus Importer:2024-09-06
Keywords: Co-base superalloys; Deformation mechanisms; Phase transformations; Stacking faults; Transmission electron microscopy